Physiological effect products in the cut rose production – application and growth - Neres da Silva, Maria de Lourdes; Barbosa, Mayara Suzanne de Melo; Lima, Raylla da Rocha; Ferreira Sabino, João Henrique; Ramos, Anamaria Ribeiro Pereira; Beckmann-Cavalcante, Márkilla Zunete (Ornamental Horticulture, 2018)
The introduction of the cut rose culture in high temperature environment requires the use of technologies that allows its acclimation to the unusual environment. Products based on strobilurins, carboxamides and anilides as well as plant regulators that promote changes in the plant growth, can be a viable tool for the introduction of cut roses in the semiarid Northeast of Brazil. Thus, the objective of this study was to evaluate the effect of products with physiological effects on the growth of cut rose ‘Ambiance’ in the Submedium of the São Francisco Valley. The experimental design was a randomized block with four replicates and six treatments: control (water application); Boscalid; Pyraclostrobin; mixture of Boscalid + Pyraclostrobin; Fluxapyroxad + Pyraclostrobin; Kinetin + GA3 + IBA; and consisted of foliar applications every 15 days for 280 days. The growth evaluations were performed through physiological indexes assessment, chlorophyll content and production of flower buds per stem. The results obtained showed that, especially Boscalid, both isolated and combined with Pyraclostrobin, the Fluxapyroxad + Pyraclostrobin and the plant regulators provided better physiological responses on the growth of the rose ‘Ambiance’, considering the relative growth rate, net assimilation rate, leaf area ratio and specific leaf area. Although the average increase on production of flower buds per stem of all treatments applied in relation to the control was in the order of 135%, none of the treatments applied produced stem for cut roses with the required commercial standards, indicating that further studies are needed for an adequate introduction of the crop in Submedium of the São Francisco Valley.